Electric sector impacts of renewable policy coordination: A multi-model study of the North American energy system. (October 2020) - Bistline, John E.T.; Brown, Maxwell; Siddiqui, Sauleh A.; Vaillancourt, Kathleen
Abstract: Policies to encourage renewable electricity generation have grown at national and subnational levels. These measures are often characterized by geographical fragmentation, as jurisdictions typically select their own renewable targets without coordinating with neighboring regions. However, the literature on renewable policies has not examined the effects of cross-border interactions and coordination, especially in a multi-model comparison to examine robustness to structural and parametric uncertainties. This paper assesses the impacts of regional and international renewable policy coordination on economic, environmental, and planning outcomes in the North American power sector. Using a multi-model comparison with eight energy-economic models, the analysis demonstrates how prospective renewable mandate trade formulations impact power sector outcomes like capacity planning decisions, costs, emissions, trade, and infrastructure investments. Model results suggest that renewable policy coordination can lower costs by up to 20% for the stringencies examined here. Fragmentation lowers gas-fired generation, but coal and nuclear are also displaced, especially when regions comply without trade. Policy costs decrease for the U.S. with higher regional and international coordination, but magnitudes vary by model. Restricting coordination leads to higher capacity investments, and absent incentives to enhance efficiency, grids do not share resources to balance variability. Transmission investments and trade are highest with international policy coordination. Highlights: We assess impacts of renewable policy coordination using a multi-model comparison. Trade provisions impact power sector planning decisions, costs, and emissions. Renewable policy coordination can lower costs by up to 20%.